2015
DOI: 10.1105/tpc.114.135780
|View full text |Cite
|
Sign up to set email alerts
|

GAP Activity, but Not Subcellular Targeting, Is Required for Arabidopsis RanGAP Cellular and Developmental Functions

Abstract: The Ran GTPase activating protein (RanGAP) is important to Ran signaling involved in nucleocytoplasmic transport, spindle organization, and postmitotic nuclear assembly. Unlike vertebrate and yeast RanGAP, plant RanGAP has an N-terminal WPP domain, required for nuclear envelope association and several mitotic locations of Arabidopsis thaliana RanGAP1. A double null mutant of the two Arabidopsis RanGAP homologs is gametophyte lethal. Here, we created a series of mutants with various reductions in RanGAP levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
(81 reference statements)
2
14
0
Order By: Relevance
“…Among the genes involved in cell growth and division, Ca_23740 (two-component response regulator, putative), Ca_07830 (RAN GTPase-activating protein 1, putative), Ca_04862 (C-methyltransferase), Ca_26707 (myosin, putative), Ca_03762 (TKL_IRAK_CrRLK1L), Ca_06937 (OsGH3.1 - probable indole-3-acetic acid-amido synthetase) and Ca_21133 (expansin precursor), were included. Two-component mediated regulation of cell division in meristems 53 , 54 , requirement of RanGTPs for mitotic cell division in female gametophyte 55 , 56 , role of sterol methytransferase mediated induction of ectopic endoreduplication 57 , 58 and the role of myosin in phragmoplast assembly during cell division 59 , 60 have been reported in different studies. Previous studies have shown that receptor like kinases 61 , 62 and auxin signaling play crucial roles in cell division and cell expansion in the meristematic tissue 63 , 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes involved in cell growth and division, Ca_23740 (two-component response regulator, putative), Ca_07830 (RAN GTPase-activating protein 1, putative), Ca_04862 (C-methyltransferase), Ca_26707 (myosin, putative), Ca_03762 (TKL_IRAK_CrRLK1L), Ca_06937 (OsGH3.1 - probable indole-3-acetic acid-amido synthetase) and Ca_21133 (expansin precursor), were included. Two-component mediated regulation of cell division in meristems 53 , 54 , requirement of RanGTPs for mitotic cell division in female gametophyte 55 , 56 , role of sterol methytransferase mediated induction of ectopic endoreduplication 57 , 58 and the role of myosin in phragmoplast assembly during cell division 59 , 60 have been reported in different studies. Previous studies have shown that receptor like kinases 61 , 62 and auxin signaling play crucial roles in cell division and cell expansion in the meristematic tissue 63 , 64 .…”
Section: Resultsmentioning
confidence: 99%
“…For the Y2H assay, the genes of interest in pDONR221 (TPXL2 and TPXL3) or pDONR207 (AUR1 and AUR2; Van Damme et al, 2004b) were Gateway-recombined into pDEST22 (GAL4 AD fusion) and pDEST32 (GAL4 BD fusions) vectors. The 35S::RanGAP1-TagBFP2 construct was generated by Multisite LR reaction into pB7m34GW using pr35S in pDONRP4P1R, RanGAP1 in pDONR221 (Boruc et al, 2015), and TagBFP2 in pDONRP2P3R. To generate the TAP tag constructs for AUR1 and AUR2, TAG-ORF and ORF-TAG constructs (under control of the constitutive cauliflower tobacco mosaic virus 35S promoter) were generated by the Gateway recombination as previously described: N-and C-terminal GS TEV tag (Bürckstümmer et al, 2006;Van Leene et al, 2008) fusions with AUR1 and AUR2, and C-terminal GS RHINO tag (Van Leene et al, 2015) and GS YELLOW tag (Besbrugge et al, 2018) fusions with AUR1 were constructed.…”
Section: Tap Constructs Y2h Constructs and Fluorescent Fusionsmentioning
confidence: 99%
“…Although many studies on NPC components and importins have suggested the importance of nucleocytoplasmic transport in plant reproduction (Blanvillain et al, 2008;Tamura and Hara-Nishimura, 2014;Boruc et al, 2015;Cui et al, 2016), no mechanistic insights have been obtained. We show here that Arabidopsis IMB4, an importin b, is critical for ovule development through mediating the nucleocytoplasmic transport of GIFs.…”
Section: Discussionmentioning
confidence: 99%